PARAMETRIC SYNTHESIS OF STABLE FAMILIES OF DYNAMIC SYSTEMS - A. A. Nesenchuk; A. I. Osipyan; S. M. Fedorovich (Наука и техника)
Stability of dynamic systems with interval uncertainty is considered in the paper. The system model is developed in the form of the root portrait represented by the family of root loci. System behavior at the stability boundary is investigated and portrait dynamics regularities at this boundary are determined. Conditions are formulated, which allow to determine parameters’ values when system stability is achieved.